Knowledge and attitudes toward HIV, hepatitis B virus, and hepatitis C virus infection among health-care workers in Malawi - Jasintha Mtengezo; Haeok Lee; Jonathan Ngoma; Susie Kim; Teri Aronowitz; Rosanna DeMarco; Ling Shi (Elsevier, 2016)
Objective: The highest prevalence of HIV infection occurs in Sub-Saharan Africa and hepatitis B virus (HBV), and hepatitis C virus (HCV) prevalence are the second highest in Sub-Saharan Africa including Malawi. Health-care workers (HCWs) play an important role in the prevention of, response to, and management of these infectious diseases. There is, however, no published research about the level of knowledge and attitudes toward HIV, HBV, and HCV infection among Malawian HCWs. The purpose of this study was to explore and determine the knowledge of and attitudes toward HIV, HBV, and HCV among a targeted population of Malawian HCWs. Methods: A cross-sectional community-based participatory research with 194 HCWs was completed employing health survey method. The project was a collaborative effort between nursing faculties in the USA and Malawian. A one-way analysis of variance (ANOVA) with the Bonferroni adjustment for multiple comparisons was used to assess the differences in knowledge and attitude among three subgroups of HCWs. Results: Of 194 of Malawian HCWs surveyed, 41% were support staff, 37% were nursing students, and 22% were health-care professionals. Both health-care professionals and support staff had high knowledge scores related to HIV/AIDS, and their attitudes were mainly positive. However, a series of one-way ANOVAs revealed significant differences in knowledge and attitude toward HIV/AIDs, HBV, and HCV among HCWs (P < 0.01). The majority had less knowledge about HBV and HCV and more negative attitudes toward hepatitis. Conclusions: This study highlights the ongoing need for reducing negative attitudes toward HIV, HBV, and HCV; and providing health education among HCWs, especially focusing on HBV and HCV prevention. The findings of the research project can be used to develop interventions addressing low HBV- and HCV-related knowledge and attitudes.